Idea: From Realism to Idealism - Piotr Jaroszyński (Studia Gilsoniana)
This paper explores the origins of the dispute “realism or idealism,” which began in philosophy from Plato and Aristotle. Passing over early-modern and modern “isms” and various meanings of the term “idea,” deep in the past we discover the Proto-Indo-European “id” as the root involving the act of seeing and the object that is seen. Ancient Greek ideín, idéa, eído and eidos, all stemming from that primitive source, were part and parcel of Greek colloquial and literary language. Plato’s Euthyphro, and one particular moral dilemma, was the ground on which idéa was introduced to philosophy, albeit the concept was the main concern (“What is holiness?”), while the term was but a makeshift solution at the time. The search for ideas that followed has moved ever further away from the material and sensually cognizable reality, even though it always started with the reality of seeing and of that which was seen. The real being (to ti en einai) required abstracting the content for the intellect to work with. Ideas, and all the more idealism, needed dialectics.